(untitled) (Argos, 2025)
The tragedy Ajax of Sophocles allows to make an analysis of the tragic emotions described by Aristotle in Poetics, taken place through the reception of the work of art and by means of the cathartic process. The scarce existent archaeological testimonies about the reception mechanism of the Greek drama confer even bigger importance to the possibility of observing the cathartic process in action, represented, in the tragedy, through the procedure of "setting in abyss" and by means of the opposition in scene of two different ways of making the mimesis of an action: narrating and making the characters work.